Effect of nutrient sources and weed control measures on quality and yield of baby corn (Zea mays) - Barod, Niranjan Kumar; Dhar, Shiva; Kumar, Ashok; Das, Dilip Ranjan (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2008 at the Experimental Farm of Divisionof Agronomy, Indian Agricultural Research Institute, New Delhi. The study was planned to assessthe effect of nutrient sources and weed control measures on yield and quality of baby corn. Thesignificantly higher husked and dehusked cob yields (4.43 t/ha and 2.15 t/ha, respectively) wereobtained with the application of N through vermicompost as compared to N applied through leafcompost, FYM and fertilizer. Significantly higher protein and sugar concentration were also obtainedwith the application of N through vermicompost. In case of weed control measures, the highesthusked and dehusked cob yield (4.29 t/ha and 2.18 t/ha respectively) and maximum concentrationof protein and sugar was recorded in weed free treatment which was at par with two hand weedingat 20 and 40 days after sowing (DAS) or pre emergence application of tank mixed atrazine @ 0.5 kgand pendimethalin @ 0.75 kg/ha.